Zinc‐Ion Batteries: 2D Amorphous V2O5/Graphene Heterostructures for High‐Safety Aqueous Zn‐Ion Batteries with Unprecedented Capacity and Ultrahigh Rate Capability (Adv. Energy Mater. 22/2020). Issue 22 (9th June 2020) - Wang, Xiao; Li, Yaguang; Wang, Sen; Zhou, Feng; Das, Pratteek; Sun, Chenglin; Zheng, Shuanghao; Wu, Zhong‐Shuai
Abstract : In article number 2000081, Zhong‐Shuai Wu and co‐workers present a novel 2D heterostructure of ultrathin amorphous V2 O5 uniformly grown on graphene for high‐safe, high‐capacity and long‐life aqueous zinc‐ion batteries. Such 2D heterostructures with strong synergy provide an effective strategy for the construction of safe, high‐performance energy storage devices.